Evaluation for the anti-urolithiatic activity of Launaea procumbens against ethylene glycol-induced renal calculi in rats - Atul Makasana; Vishavas Ranpariya; Dishant Desai; Jaymin Mendpara; Vivek Parekh (Toxicology Reports, 2014)
Launaea procumbens Linn. is a plant commonly found in the west India and has been reported to decrease the renal calculi. This study investigated the anti-urolithiatic activity of L. procumbens against ethylene glycol-induced urolithiasis and its possible underlying mechanisms. The crude methanolic extract of L. procumbens leaves was studied using ethylene glycol-induced renal calculi in rat model. Results indicate that ethylene glycol feeding to rats resulted in to hyper oxaluria, hypercalciuria, as well as increased renal excretion of phosphate. Supplementation with methanolic extract of L. procumbens leaves (MELP) significantly prevented changes in urinary calcium, oxalate and phosphate excretion dose-dependently. The increased calcium and oxalate level and number of calcium oxalate crystal in the kidney tissue of calculogenic rats were significantly reverted by supplementation with MELP. The MELP supplementation also prevents the impairment of renal functions. The mechanism underlying this effect is mediated possibly through antioxidant nephroprotection and its effect on urinary concentration of stone forming constituents and risk factor. Conclusion: These results indicate that methanolic extracts of L. procumbens leaves are effective against the urolithiasis.